PERFORMANCE ENHANCEMENT OF PEROVSKITE SOLAR CELL FASnI3/FAGeCI3 - Guenou, Nesrine; VILBOIS Leila.Amal (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2024)
Inorganic perovskite solar cells have attracted significant attention for their remarkable efficiency in converting sunlight into electricity. yet, their widespread adoption has been hindered by the toxicity of lead. This study addresses this challenge by exploring FASnI3 as a lead-free and environmentally friendly alternative. Using SCAPS software, we modeled the device structure of (FTO/n-FASnI3(ETL)/i-FASnI3 /p-FAGeCl3(HTL)/Au) and achieved an initial efficiency of 20.42%. To further improve performance, we added a strongly n-doped layer n+ -FASnI3 , which increased efficiency to 21.07%. And by varying the thickness and doping levels of (i-layer, nlayer, p-layer, and ( n +FASnI3), we achieved the highest simulated efficiency of 24.10%. These results highlight FASnI3 as a promising lead-free alternative capable of exceeding the efficiency of conventional lead-based inorganic perovskite solar cells, paving the way for a more sustainable and environmentally friendly future in solar energy.
Microelectronic